THE JUSTIFICATION OF DEVELOPMENT OF INTEGRATIVE MODEL OF SOCIAL EMOTIONAL COMPETENCE - Elsiņa, Inese; Perepjolkina, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Social emotional competence (SEC) is called as one of the most needed competences of 21st century. In the past dozen years, number of researches about SEC’s relationship to many other crucial outcomes in psychosocial life of individual –performance, school readiness, success in participation and interaction with peers and adults, well-being, different clinical variables, in example, learning disabilities, depression, anxiety, withdrawal behavior etc. –have been published. Nevertheless, there is no agreement about the definition of SEC, which components comprises it, and there is no standardized measure for SEC assessment. There hasn’t been sufficient qualitative scientific discussion about the topic in Latvia as well, although SEC or its components have been frequently researched here. The aim of this article was to provide a theoretical overview of the problems and challenges in SEC research in general and to justify the need of development of integrative model of SEC. The main objective was to develop its preliminary theoretical version.